Precipitation Solvents for RNA Extraction of Dengue Virus Type 3: Dimethylformamide, Ethylenediamintetraacetic Acid, and Ultrapure H2O - Rizqidhana Juliana Putri; Teguh Hari Sucipto; Harsasi Setyawati; Siti Churrotin; Ilham Harlan Amarullah; Puspa Wardhani; Aryati Aryati; Soegeng Soegijanto (Universitas Airlangga, 2018)
Dengue is a disease caused by a virus from the family Flaviviradae, carried by a female mosquito of Aedes aegypti species. Dengue fever is widespread in the tropic areas. It caused by rainfall, temperature and unplanned urbanization. According to the ministry of health , almost all provinces in Indonesia are endemic areas of dengue fever. In 2014, up to mid-December Dengue Hemorrhagic Fever (DHF) patients in 34 provinces in Indonesia are 71,668 people and 641. This figure is lower than the previous year, 2013 with 112,511 people and 871 deaths . This disease consists of four types of serotypes, namely DENV-1, DENV-2, DENV-3, and DENV-4. This disease can be identified using a variety of methods, one of the method is Reverse Transcription - Polymerase Chain Reaction (RT-PCR) method. This study aims to determine the ability of Dimethylformamide (DMF), Ethylenediamintetraacetic Acid (EDTA), and Ultrapure H2O as the substitute of Ethanol for precipitation in RNA extraction process. The sample used in this research obtained from Surabaya. RNA extraction itself can be done by using a special kit for RNA extraction. In Reverse Transcription - Polymerase Chain Reaction method, first RNA is extracted and then transcribed back (Reverse Transcription) which then form cDNA that later will be amplified by using PCR method. In this study used specific primers for dengue virus type 3 (DENV-3). The results of this study show that DMF, EDTA, and Ultrapure H2O can be used as the substitute of Ethanol for precipitation on RNA extraction. The result is evidenced by the formation of viral DNA bands on gel electrophoresis results.